Thyroid Hormone Levels in Preterm Neonates with Birth Weight Less than 2500 g, Treated with Phenobarbital - bidabadi, Elham; Zarkesh, Marjaneh; Mirzaii Chaghakabudi , Maryam (Iranian Journal of Child Neurology, 2023)
Objectives Indicatively, phenobarbital can impair thyroid function in adults and children. The present research aims to evaluate the thyroid hormone levels in preterm neonates who had received phenobarbital treatment. Materials & Methods This study was conducted on preterm neonates who weighed less or equal to 2500 g when phenobarbital was prescribed for treatment in the first 15 days of life. TSH and total T4 measurements were performed before and three months after initiation of phenobarbital. Results In this study, the sum of preterm neonates stood at 94, of which 53 were girls, with a mean birth weight of 2004.41 ± 315.41g. Weight of 8.5% were under 1500 g. The mean gestational age was estimated at 33.64 ± 2.01 weeks. Mean T4 levels were 12.24 ± 1.96 and 12.07 ± 1.95 (p=0.334), and mean TSH levels were 5.34 ± 2.14 and5.15 ± 2.15 (p=0.376) before and after prescribing phenobarbital, respectively. The same results were compared based on sex, gestational age, birth weight, and height for T4 and TSH and T4 based on head circumference. The only significant difference was TSH in preterm infants with head circumference <32 cm before and after prescribing phenobarbital (p=0.030). Conclusion In preterm newborns that had less than 2500 g birth weight, phenobarbital did not significantly alter the serum thyroid hormone levels